Smart Home System: A Comprehensive Review. (21st March 2023) - Chakraborty, Arindom; Islam, Monirul; Shahriyar, Fahim; Islam, Sharnali; Zaman, Hasan U.; Hasan, Mehedi
Abstract : Smart home is a habitation that has been outfitted with technological solutions that are intended to provide people with services that are suited to their needs. The purpose of this article is to perform a systematic assessment of the latest smart home literature and to conduct a survey of research and development conducted in this field. In addition to presenting a complete picture of the current smart home system's (SHS) development and characteristics, this paper provides a deep insight into latest hardware and trends. The research then moves on to a detailed discussion of some of the important services provided by the SHS and its advantages. The paper also statistically discusses the current and future research trends in the SHS, followed by a detailed portrayal of the difficulties and roadblocks in implementing them. The comprehensive overview of the SHS presented in this paper will help designers, researchers, funding agencies, and policymakers have a bird's-eye view of the overall concept, attributes, technological aspects, and features of modern SHSs.